2015
DOI: 10.1039/c5ra04188k
|View full text |Cite
|
Sign up to set email alerts
|

Chemical interactions between zirconium and free oxide in molten fluorides

Abstract: The chemical interactions between zirconium and free oxide in FLiNaK melts at different zirconium to oxide (n Zr /n O ) molar ratios were studied by means of a carbothermal-reduction technique (LECO oxide analyzer) and Raman spectroscopy. ZrO 2 precipitates were formed with n Zr /n O # 0.5, while ZrO 2 was converted to Zr 2 OF x 6Àx complexes with n Zr /n O > 0.5. The maximum amount of Zr 2 OF x 6Àx complexes in FLiNaK melts was found to be 0.020 mol kg À1 . With an initial oxide concentration lower than 0.020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Fluoride eutectic salts have been studied extensively as a coolant or a fuel salt for nuclear reactor systems due to their ability to act as an effective heat transfer uid at high temperature and low pressure and based on high radiation ux. [1][2][3][4] Specic to the fuel salt, the concentration of free oxygen dianion O 2À is rigorously regulated to avoid UO 2 [5][6][7] being precipitated. As reported by Oak Ridge National Laboratory (ORNL), the zirconium tetrauoride (ZrF 4 ) can act as the O 2À absorber additive in fuel salts for removing free O 2À and avoiding UO 2 being precipitated.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride eutectic salts have been studied extensively as a coolant or a fuel salt for nuclear reactor systems due to their ability to act as an effective heat transfer uid at high temperature and low pressure and based on high radiation ux. [1][2][3][4] Specic to the fuel salt, the concentration of free oxygen dianion O 2À is rigorously regulated to avoid UO 2 [5][6][7] being precipitated. As reported by Oak Ridge National Laboratory (ORNL), the zirconium tetrauoride (ZrF 4 ) can act as the O 2À absorber additive in fuel salts for removing free O 2À and avoiding UO 2 being precipitated.…”
Section: Introductionmentioning
confidence: 99%
“…Besides,Gibilaro 18 has found that the addition of calcium oxide (CaO) into a ZrF 4 -containing lithium uoride-calcium uoride (LiF-CaF 2 ) salt leads to the formation of a close to equimolar mixture of solid ZrO 2 and ZrO 1.3 F 1.4 . Korenko et al19 and our previous studies7,8,16,20 have used X-ray diffraction (XRD) phase analysis and electrochemical techniques and discovered the ZrO 2 formation when oxide contamination occurs in the ZrF 4 -containing systems (i.e., LiF-NaF-KF-ZrF 4 and LiF-NaF-KF-UF 4 -ZrF 4 ), whereas only UO 2 is observed in the systems without ZrF 4 (i.e., LiF-NaF-KF-UF 4 and LiF-BeF 2 -UF 4 ). These studies demonstrate that O 2À in zirconium-based systems can be reduced by forming Zr(IV) oxide or oxyuorides, preventing the UO 2 precipitation.…”
mentioning
confidence: 51%
“…2, which was described in detail in our previous studies. 7,8,16,17,20,21,24 The whole experiment was conducted in a glove box protected by dry argon atmosphere (99.999%), and the oxygen and water contents in the glove box were both strictly controlled below 0.5 ppm.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations